2008
DOI: 10.4028/www.scientific.net/msf.584-586.597
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Property of Submicrocrystalline Pure Fe Produced by HPT-Straining

Abstract: The microstructure and the mechanical properties of pure Fe after HPT-straining at a rotation-speed of 0.2 rpm under a compression pressure of 5 GPa were investigated. The elongated grains with 300 nm thick and 600 nm long were observed at r = 1.5 mm away from the disk center regions after HPT-straining for 5 turns ( εeq = 45). The obtained Vickers microhardness in the submicrocrystalline Fe after 5 turns was around Hv 3.6 GPa. The engineering tensile strength and total elongation of the HPT-processed Fe for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 31 publications
4
28
0
3
Order By: Relevance
“…9(a) is less than the values reported in earlier works of Fe. [15][16][17][18][19][20] This can be attributed to the difference in carbon contents in the materials employed in individual experiments. Although the C content was not described explicitly except the study of Todaka et al, 16) which is 0.03% C, it must have been much higher than 11 ppm in the Fe used in this study.…”
Section: Evolution Of Mechanical Properties and Microstructures With mentioning
confidence: 99%
See 2 more Smart Citations
“…9(a) is less than the values reported in earlier works of Fe. [15][16][17][18][19][20] This can be attributed to the difference in carbon contents in the materials employed in individual experiments. Although the C content was not described explicitly except the study of Todaka et al, 16) which is 0.03% C, it must have been much higher than 11 ppm in the Fe used in this study.…”
Section: Evolution Of Mechanical Properties and Microstructures With mentioning
confidence: 99%
“…Although the C content was not described explicitly except the study of Todaka et al, 16) which is 0.03% C, it must have been much higher than 11 ppm in the Fe used in this study. Very recently, Todaka et al 20) reported extraordinarily high tensile strength in the same high purity Fe after processing by HPT. The enhancement results in almost twice when compared with the present tensile strength despite the fact that the hardness is in almost the same level as the preset study.…”
Section: Evolution Of Mechanical Properties and Microstructures With mentioning
confidence: 99%
See 1 more Smart Citation
“…7,8) The material was annealed at 1273 K for one hour in pure argon atmosphere, and then cut and polished into discs of 10 mm in diameter and 0.85 mm in thickness for HPT-straining. The HPT process was carried out using anvils with a depression of 0.25 mm in depth and of 10 mm in diameter.…”
Section: Methodsmentioning
confidence: 99%
“…The Vickers hardness of HPTprocessed metals increases significantly with increasing the equivalent strain at the initial stages of straining, but saturates to constant values at certain strains. 5,6) It has been reported by Todaka et al 7,8) that the HPT-processed ultra-low carbon steel exhibited extraordinary high strength and ductility.…”
Section: Introductionmentioning
confidence: 99%